Millennial generation preferences in food and the effects on willingness to pay - Ho, J (2015)
The purpose of the study is to determine motivations behind millennial food purchase decisions and preferences. These purchase preferences are compared with willingness to pay (WTP) in order to find which food motivations increase or decrease the millennials willingness to pay. A consumer survey that targeted millennials was conducted with a sample size of 100. The survey used semantic differential questions to ask the respondents to rate a number of food motivations in order to find any food preferences. Factor analysis was performed to sort the food preferences into domains. A second part of the survey asked the respondents to rate the maximum willingness to pay for a meal with various foods preference conditions. Regression analysis was run with the semantic differential questions and the willingness to pay. Results show that companies have a reputation of cheap prices, ease of pick up and reputation of being authentic have negative effect on the willingness to pay of millennials. Food being aesthetically pleasing, having access to drive through and organic food has positive effects on the willingness to pay. There were factor domains that resembled the predicted domains of excellence, morality, efficiency, aesthetics and esteem; however the factor domains that were predicted failed to show many meaningful relationships with willingness to pay. This may be due to a number of limitations with the methodology and the sample size used. Practical implications include understand the food motivational factors that are likely to increase willingness to pay into marketing and business practices and promoting high willingness to pay factors such as aesthetically please and organic when they are relevant to the food being sold.